Flow‐disturbance considered simulation for algae growth in a river–lake system. Issue 4 (6th August 2015) - Wang, Hua; Zhou, Yiyi; Xia, Kun; Yang, Rui; Liu, Xiaodong
Abstract: A 1‐D–2‐D coupled numerical model embedded with the impact of hydrodynamic conditions on algae growth was developed to simulate the algae concentration for a river–lake system. Based on the laboratory experiment and field investigation, the 'flow‐disturbance parameter α' was presented to improve the algae growth formula. By numerical simulation, the algae growth processes in a river–lake system were simulated, and the temporal and spatial distributions of Chl‐a concentration in the area were analysed. Our results show the following: (1) Hydrodynamic conditions play an apparent effect on algae growth. A suitable turbulence is more beneficial for algal proliferation than the static or intense mixing. (2) In the studied area, the flow disturbances in the east–west rivers are generally stronger than that in the north–south rivers, while the Chl‐a concentration is oppositely distributed in the river networks. (3) As a result of the different flow disturbance intensities during periods, the algae cell density in all investigated sections also alters evidently along with the seasons. The average Chl‐a concentration in the dry seasons (November–April) increased by 9.22% than that in the flood seasons (May–October). (4) From the point of the whole river–lake system, the dynamic conditions in the lake inlet areas are more suitable for algae growth than that in the river networks. The Chl‐a concentrations of S2 and S4 are averagely increased by 18.5% than that in the river networks. Copyright © 2015 John Wiley & Sons, Ltd.